Growth curves, body nutrients deposition and determination of protein requirement for light and semi heavy hen pullets - Silva, José Humberto Vilar da; Filho, José Jordão; Silva, Edson Lindolfo da; Costa, Fernado Guilherme Perazzo; Naves, Patricia Emília Givisiez; Figueiredo-Lima, Denise Fontana; de Siqueira, Jefferson Costa; Lima, Rodrigo Barbosa (Scientia Agraria Paranaensis, 2017)
The aim of this work was to determine growth curves and body nutrients deposition by using Gompertz equation, and to estimate protein requirement in light and semi heavy hen pullets. In total, 1,500 hen pullets were distributed at random into 30 repetitions of 25 birds each. Experimental period was divided into three steps (1st to 4th, 5th to 11th and 12th to 16th weeks of age). Rations were formulated based on corn and soybean meal and offered ad libitum. Birds were weighed weekly. Two birds per repetition were used to determine chemical body composition and data were used to obtain Gompertz model parameters. Allometric ratios were used to describe changes in the body composition in protein, lipid, mineral matter and water in the eviscerated and featherless body. Weight-age data of Dekalb White and Bovans Goldline pullets were well described by Gompertz function. Allometric coefficients of fat, water and mineral matter in function of the protein body weight were, respectively: 0.114, 0.811 and 0.930 for Dekalb line and 1.160, 0.429 and 0.189 for Bovans line. There are differences between lines for growth rates and body nutrients and feathers deposition, with Dekalb line being the most precocious. Total protein requirements (maintenance and growth) for pullets from 1st to 4th, 5th to 11th and 12th to 16th weeks of age were 4.41; 9.814 and 12.612 g˙d-1 for Dekalb White and 4.82; 8.859 and 7.673 g˙d-1 for Bovans Goldline, respectively.